Информационные возможности цифровой обработки радиосигналов с известной несущей частотой - Рогожкин, Евгений Васильевич; Белозёров, Д. П.; Ерёмин, А. Н. (НТУ "ХПИ", 2003)
In modern conditions the fundamental part of signal processing is carried out by a means of digital computer technology. Thereof the digital systems of processing appear by more flexible, that allows to adapt for varied conditions, and thus in the large degree exclude mistakes of analog transformation. In paper the possibilities of the shortest transition from analogue processing (reception, amplification) to digital representations are considered. Signal, at which there are noticeable losses of the information
Keywords: амплитудная модуляция; радиолокационные измерения; радиолокация; радиовещание; синхронное детектирование; ФМ-сигналы; частота; спектр рассеяния